Traditional Wushu in the Modern Era: Challenges and Opportunities (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Traditional Wushu, a centuries-old martial art, faces numerous challenges in the modern era. This article explores the current state of Traditional Wushu, examining the impact of globalization, commercialization, and cultural evolution. We identify key challenges, including the erosion of traditional values, the rise of modernized Wushu forms, and the need for cultural preservation. Despite these challenges, opportunities exist for Traditional Wushu to thrive, including its potential for cultural exchange, physical education, and personal development.